SOJIWAN TEMPLE RELIEF AS AN INSPIRATION FOR CERAMIC ARTWORK - Arisutta, Dona Prawita; Adi, Sigit Purnomo (Acintya, 2024)
This study explores the reception of monkey and crocodile figures depicted on one of the relief panels of Sojiwan Temple in Klaten, Central Java, Indonesia. The Sojiwan Temple reliefs visualize fairy tales from the Jataka, a collection of fables that often convey contextual and didactic themes. Through the lens of reception theory, this study identifies life lessons such as intelligence, dexterity, impartiality, and wisdom from the narrative panels of Sojiwan Temple and transforms them into ceramic art. Three ceramic artworks inspired by the monkey and crocodile reliefs highlight the notion that even a simple fairy tale does not possess a single, fixed meaning. Instead, there is a progressive interpretation that evolves with each reading of the reliefs at Sojiwan Temple. This research concludes that ceramics can serve as a medium to convey diverse interpretations, thereby enriching the aesthetic appreciation of the monkey and crocodile reliefs at Sojiwan Temple. Keyword: Monkey and Crocodile Relief, Sojiwan Temple, Life Learning, Reception Theory, Ceramic Art